Pengaruh Loneliness dan Self-Control Terhadap Online Game Addiction - Bahren, Sindi Zhafirah Shabrina; Rosyidi, Hamim (Journal of Research and Measurement in Psychology: JPPP, 2024)
The development of information technology has brought various conveniences to everyday life, including easier access to online games. However, a negative impact that is often overlooked is online game addiction which can adversely affect a person's physical, mental and social health. The purpose of this study is to understand the influence of loneliness and self-control on online game addiction in gaming community members. This study used a correlational quantitative approach with 220 research subjects from the online gaming community. This study used the OGA scale from Lemmens (2009) to measure online game addiction variables, UCLA Loneliness Scale Version 3 from Russel (1996) to measure loneliness variables, and Self-Control Scale (SCS) from Tangney (2004) to measure self-control variables. The results showed that there is a significant influence between loneliness and self-control on online game addiction.